BREEDING OF A NEW TYPE OF SIMMENTAL BEEF CATTLE IN THE CARPATHIAN REGION OF UKRAINE - Шпак, Л.В.; Казьмірук, Л.В.; Калинка, Андрій; Прилипко, Татьяна (SWorldJournal, 2022)
For the first time, the article highlights the issue of the efficiency of cattle breeding of a new population Bukovyna zonal type of meat polled Simmental ruminants, which is relevant in the Carpathian region of Ukraine.The results of research have showe